HEART RATE LEVELS IN THE POPULATIONS OF THE RUSSIAN FEDERATION AND THE UNITED STATES OF AMERICA DURING THE THIRTY-YEAR PERSPECTIVE - S. A. Shalnova; V. G. Vilkov; A. V. Kapustina; A. D. Deev (Рациональная фармакотерапия в кардиологии)
Heart rate (HR) acceleration is one of the risk factors of the number of prevalent chronic non-communicable diseases.Aim. To evaluate changes in mean levels of HR in the Russian Federation (RF) and the United States of America (USA) in different age and sex groups from 1975 to 2014.Material and methods. HR levels in men and women of different age groups were evaluated in the populations of the RF and the USA in 1975-1982 and in 2007-2014 by the secondary analysis of cross-sectional trials data. A total number of cases was 48974.Results. In 80th years of XX century Russian men and women of all age groups had lower HR as compared to the USA, the distinctions were statistically significant in all age groups except for men aged 25-34 years (p<0.0001). During the next 3 decades HR significantly decreased in all groups of the USA population, while the RF population demonstrated variety of HR levels trends in different groups, absolute distinctions in mean values were relatively small and did not exceed 2 beats per minute. At the present time HR levels are less in the RF as compared to the USA in women aged 25-55 years and in men aged 25-34 years; in 55-64-year old men HR is somewhat higher in the RF than in the USA, other groups revealed statistically insignificant distinctions.Conclusion. The USA evidently loosed out to the RF in mean levels of HR in all age groups 35 years earlier. During the next 3 decades situation has been worsened as applied to the RF and distinctions with the USA have been largely smoothed over.